아시아의 타투 Tattooed Asia - Boo, Kyung-hwan; Cho, Hyeon-jong; Jeong, Ji-hee; Kim, Mi-jeoong; Boo, Kyung-hwan ([Korea (South)] National Asia Culture Center, 2018)
Based on the results conducted by the Asian Culture Research Institute, this book is a supplement and reorganization of the contents of the exhibition of the same name held at the National Asia Culture Center from November 25, 2017 to July 29, 2018, in book form. It contains various materials and archives, such as relics, literature, illustrations, and photographs, on the history and culture of tattoos in various region of the world, as well as field research on major tattoo cases in Asian regions, such as Thailand, the Philippines, Taiwan, and Japan.
1. Tattoos of ancient humans -- 2. Tattoos around the world - Pacific/Asia -- 3. Tattoos of the World II - America, Europe, Middle East, Africa, etc. -- 4. Thai witchcraft tattoo Sakyan -- 5. Southeast Asian ethnic tattoos -- 6. Taiwanese Pai Wan hand tattoo -- 7. Japanese painting tattoo Horimono
Keywords: Tattooing; Tribal tattoos